Размещение кругов и невыпуклых многоугольников с поворотами в прямоугольнике минимальной длины - Злотник, М.В.; Стоян, Ю.Г. ("Доповіді НАН України", 2007)
A mathematical model of the optimization placement problem of circles and non-convex polygons with rotations into a rectangle of minimal length is built, and its peculiarities are investigated. An algorithm of solving the problem is developed. This algorithm allows one to get an approximation to the global minimum of the problem. A numerical example is given.